The Continuous Traumatic Stress Syndrome - The Single Therapeutic Interview - Straker, Gill; Sanctuaries Counselling Team (PINS-Psychology in Society, 1987)
The term post-traumatic stress syndrome is a misnomer in the South A£r1can context. Individuals living in South Africa’s black townships are subjected to continuous traumatic stress. This stress is occasioned by the high levels of violence in the townships, violence which is contributed to by confrontations between (a) the South African Defence Force and Police and various sectors of the community; (b) black anti-apartheid groups and black right wing vigilantes who are more supportive of the status quo; and (c) inter-group fighting among rival anti-apartheid groups e.g. UDF and Azapo.